The challenge of accounting for individual differences in folk-economic beliefs. (30th August 2018) - Ruisch, Benjamin C.; Anderson, Rajen A.; Pizarro, David A.
Abstract: We argue that existing data on folk-economic beliefs (FEBs) present challenges to Boyer & Petersen's model. Specifically, the widespread individual variation in endorsement of FEBs casts doubt on the claim that humans are evolutionarily predisposed towards particular economic beliefs. Additionally, the authors' model cannot account for the systematic covariance between certain FEBs, such as those observed in distinct political ideologies.